PENGEMBANGAN MINA PADI SEBAGAI BAHAN PANGAN DAN WISATA DI DESA DEMANGREJO - Pawana, Sekhar Chandra (Jurnal Atma Inovasia, 2022)
The 80th period of KKN program was held with the theme Society 5.0 as a response to the COVID-19 pandemic. The activity was attended by Atma Jaya Yogyakarta University students as an obligation. Participants were divided into groups of students that came from different faculties. KKN would be held from October 1st to December 4th, 2021 virtually. The authors were members of group 101 who were given the responsibility to expand their knowledge and skills through the experiences in Demangrejo Village, Sentolo District, Kulon Progo Regency. Demangrejo village itself have had potential in agricultural land, rice fields in the north which stretched along 1.68 km. Good irrigation in rice fields came from the Progo River and wells around the village. Therefore, most of the villagers were farmers. Because of those reasons, village welfare improvement could be achieved by developing existing agricultural land into mina padi. Mina Padi is a combination of rice cultivation and fish cultivation. These two aspects would support each other in terms of production. The water quality of the rice fields would improve and the fish seeds would get their food source from the bran, milled rice husk. When it's time to harvest, the results will be more profitable for the village because it is a combination from 2 types of cultivation in the same period. Beside improving the economic aspect of the village, Mina Padi was also expected to play a role in improving Demangrejo Village's tourism.